Recent advances in metal-organic framework-based electrode materials for supercapacitors: A review. (June 2023) - Zhao, Wenbo; Zeng, Yuting; Zhao, Yunhe; Wu, Xiaoliang
Abstract: Supercapacitor (SC) is generally regarded as a promising electrochemical device in the field of energy storage. Electrode materials, as one of the components of SCs, play an important role in the electrochemical performance of energy storage devices. Thus, it is essential to look for or synthesize new electrode materials. Metal-organic frameworks (MOFs) material, as a crucial classification of new materials in metal-organic materials (MOM) has been widely studied in SCs due to their multifunctional diversities, inherent porosity, large specific surface area, tunable pore size distribution, and simple synthesis method. In this review, we present recent research advances in developing various support materials (e.g., carbon nanotube, carbon nanofiber, and metal supports) to enhance the electrochemical performance of SCs. Specially, we provide a detailed overview of the latest research advances in MOF-derived materials and composites in SCs. At last, current developments are summarized and critical challenges for driving these intriguing developments toward practical applications are discussed together with promising solutions. Graphical abstract: Unlabelled Image Highlights: MOFs-based electrode materials and some common supports are summarized. Some synthesis methods of MOFs and MOFs-based materials are discussed in detail. Challenges and perspectives of MOFs and MOFs-based materials are presented.